Impacts of Tougu Xiaotong Capsule on Chondrocytes Ultrastructure and Cartilage Matrix in Rats with Early Stage Osteoarthritis - Xiaodong LU; Ruhui LIN; Wenlie CHEN; Fangfang FENG; Yunmei HUANG; Meiya HUANG (康复学报)
Objective:To investigate the effects of Tougu Xiaotong capsule (TXC) on chondrocytes ultrastructure and cartilage matrix in rats with early stage osteoarthritis.Methods:Twenty four male rats were randomized into non-osteoarthritis group, osteoarthritis model group and TXC treated osteoarthritis model group, with eight rats in each group. The rat model of osteoarthritis was established by papain injection into knee joint cavity, and the rats received TXC aqueous solution intragastric for four weeks, then rats were sacrificed to extract the femoral condyle cartilage for sample preparation. The chondrocytes microstructure and ultrastructure in different regions were observed by electromicroscopy. The contents of proteoglycan and collagen II in cartilage matrix were analyzed by histochemical approaches.Results:Chondrocytes ultrastructure showed that the chondrocyte proliferation and clustering, and substantial reduction or swelling organelles were observed in osteoarthritis model group but not in non-osteoarthritis group. The clustering of chondrocytes was reduced, and the organelles of golgi complexes, rough endoplasmic reticulum and mitochondria were increased in TXC treated osteoarthritis model group compared to osteoarthritis model group. Cartilage matrix quantitative analysis showed that the contents of proteoglycan and collagen II in osteoarthritis model group were significantly decreased compared to non-osteoarthritis group (P<0.01); the contents of proteoglycan and collagen II were significantly increased in TXC treated osteoarthritis model group compared to osteoarthritis model group (P<0.01).Conclusion:TXC could ameliorate chondrocytes degeneration, endoplasmic reticulum and mitochondria damage, and increase the synthesis of cartilage matrix to delay the cartilage degeneration of osteoarthritis rats at early stage.